Dossier II: El marcaje intencional como método en balística identificativa - Acuña Hernández, José Daniel (Quadernos de criminología, 2022)
This article discusses the forensic interest of the intentional marking of firearms. His proposal as a method in Identifying Ballistics represents a radically different approach from his basic method. The tests carried out so far could be considered suggestive but lacking in development.